Potential and Synergy Evaluation of Indigenous Biosurfactant-Producing Bacteria from Abandoned Oil Wells for Microbial Enhanced Oil Recovery (Meor) Technology Development - Brian Saputra Manurung; Windy Natalia Nusaly; Abdul Mahid Ukratalo; Monalisa Pertiwi Jeriska Taihuttu; Fuadiska Salamena (Jurnal Biosilampari : Jurnal Biologi, 2025)
Petroleum is a non-renewable natural resource that continues to be used in many applications. However, the availability of crude oil ready for use is decreasing due to the low productivity of oil wells, one of which is caused by its high viscosity. This needs to be resolved to meet the demand for crude oil. This study aims to determine the potential of eight petrophilic bacteria in producing biosurfactants and to determine their interaction to be applied to Microbial Enhanced Oil Recovery technology. The research design in this study was a Factorial Randomized Group Design with two types of treatments: 8 types of bacteria and 4 different temperatures. The experimental units were 32, with 2 replications of each, resulting in 64 experimental units.  The observation variables in this study were the diameter of the clear zone and the interaction of bacteria. Clear zone diameter was analyzed using Analysis of Variance, then continued with Duncan's New Multiple Range Test at 5%. This study showed the formation of clear zones as an indicator of the production of biosurfactants influenced by temperature. Brevundimonas   diminuta and P. peli have superior potential in forming clear zones in hemolytic assay than other bacteria, with clear zone diameters of 26.805 mm and 26.040 mm, respectively, at 44°C of incubation. Three bacteria have a high percentage of synergy in this study of 50%, which synergized with 4 other types of bacteria.